Hydraulic traits are more diverse in flowers than in leaves. Issue 1 (18th March 2019) - Roddy, Adam B.; Jiang, Guo‐Feng; Cao, Kunfang; Simonin, Kevin A.; Brodersen, Craig R.
Summary: Maintaining water balance has been a critical constraint shaping the evolution of leaf form and function. However, flowers, which are heterotrophic and relatively short‐lived, may not be constrained by the same physiological and developmental factors. We measured physiological parameters derived from pressure–volume curves for leaves and flowers of 22 species to characterize the diversity of hydraulic traits in flowers and to determine whether flowers are governed by the same constraints as leaves. Compared with leaves, flowers had high saturated water content, which was a strong predictor of hydraulic capacitance in both leaves and flowers. Principal component analysis revealed that flowers occupied a different region of multivariate trait space than leaves and that hydraulic traits are more diverse in flowers than in leaves. Without needing to maintain high rates of transpiration, flowers rely on other hydraulic traits, such as high hydraulic capacitance, to maintain turgor pressure. As a result, instead of employing a metabolically expensive but durable carbon (C)‐based skeleton, flowers may rely predominantly on a metabolically cheaper, hydrostatic skeleton to keep their structures on display for pollinators, which has important implications for both the costs of reproduction and the biomechanical performance of flowers, particularly during drought. Abstract : See also the Commentary on this article byOlson & Pittermann, 223 : 8–10 .